Effect of cigarette smoke on aesthetic brackets: an in vitro study - BORGES,Laura (2022)
ABSTRACT Objective: The objective of this study was to evaluate the effect of cigarette smoke (CS) on physical and mechanical properties of ceramic, polycarbonate and alumina ceramic brackets. The null hypothesis tested was that aesthetic brackets would not be influenced by CS. Methods: Ninety aesthetic brackets were allocated to three groups (n = 30): ceramic (GCE), polycarbonate (GCO) and alumina ceramic (GPS). Ten samples of each group were assigned to color and surface roughness analysis, performed before (T0) and after (T1) exposure to CS; and twenty samples were allocated into control and experimental groups (n = 10) (not exposed and exposed to CS, respectively) for shear bond strength test (SBS). Exposure to CS followed an adaptation of the method described by Le Mesurier. Colorimetric reading, surface morphology and roughness, SBS and adhesive remnant index (ARI) were assessed. Statistical analysis comprised independent and paired t-tests, ANOVA/Tukey and Fisher’s exact tests (α = 0.05). Results: Changes were observed in brackets’ color (NBS: GCE = 2.4; GCO = 1.9; GPS = 2.1), surface roughness (ΔRa: GCE = 1.1 ± 0.8 µm; GCO = 1.9 ± 1.5µm; GPS = -0.3 ± 0.1 µm / ΔRz: GCE = 1.4 ± 1.0 nm; GPS = -0.5 ± 0.1 nm); and SBS (GPS - experimental = 221.8 ± 48.6 N) after exposure to CS (p< 0.05). Conclusions: Exposure, in vitro, of aesthetic brackets to CS resulted in changes of color to darker and more opaque shades, surface roughness alterations, and higher SBS values. ARI scores were not associated with exposure to CS.